2015
DOI: 10.1038/cdd.2014.241
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of single cell responses to ER stress indicates that the relative dynamics of IRE1/XBP1 and PERK/ATF4 signalling rather than a switch between signalling branches determine cell survival

Abstract: An accumulation of misfolded proteins in the endoplasmic reticulum (ER) triggers the unfolded protein response (UPR) mediated via the activation of three transmembrane proteins IRE1, PERK and ATF6. Signalling through these proteins is aimed at enhancing the ER folding capacity and reducing the folding load. If these processes fail to re-establish protein homeostasis within the ER, then cell death prevails via apoptosis. How the shift from pro-survival to pro-apoptotic signalling is regulated remains unclear wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 33 publications
(42 reference statements)
7
93
0
2
Order By: Relevance
“…The FOS HPLCprofiles could not reveal total suppression of protein synthesis by switches between these branches and PERK as the glycan Man 4 GlcNAc 1 was present in all spectra indicating a continued support of the dolichol phosphate cycle. Our findings are agreed with the idea that progression of a disease depends on dynamics of UPR branches rather than a switch between them [26].…”
Section: Fig 4 Glycomarkers Of Er Stress and Lysosomal-endosomal Sysupporting
confidence: 81%
“…The FOS HPLCprofiles could not reveal total suppression of protein synthesis by switches between these branches and PERK as the glycan Man 4 GlcNAc 1 was present in all spectra indicating a continued support of the dolichol phosphate cycle. Our findings are agreed with the idea that progression of a disease depends on dynamics of UPR branches rather than a switch between them [26].…”
Section: Fig 4 Glycomarkers Of Er Stress and Lysosomal-endosomal Sysupporting
confidence: 81%
“…XBP1s deficiency or premature attenuation of IRE1/XBP1s signaling during ER stress promotes sustained activation of PERK/CHOP and cell death. 6,12,18 Moreover, sustained IRE1/XBP1 activity enhance cell survival in conditions of severe stress, 11 further supporting a protective role for this pathway. We reported that pancreatic acinar cells express XBP1s in physiological conditions, and that Xbp1 genetic deletion in mice impairs digestive enzyme secretory responses in acinar cells, and decreases the number of zymogen granules in pancreas of ethanol-fed mice.…”
Section: Resultsmentioning
confidence: 90%
“…10 Early induction of XBP1s upon ER stress is critical for ER adaptation to stress and cell survival, while premature termination of this signal leads to ER dysfunction and cell death. 11, 12 …”
Section: Introductionmentioning
confidence: 99%
“…Unlike the protective role of IRE1α pathway in the early stages of infection, the PERK pathway plays an apoptotic role in the late stages. Similarly, an early onset of XBP-1 splicing and a slow translation of ATF4 for cell survival were observed by imaging the single cell response to ER stress (Walter et al, 2015). We also confirmed this apoptosis caused by ER stress is beneficial in controlling the number of intracellular bacteria by pre-treatment with the specific agonist and inhibitor of ER stress.…”
Section: Discussionmentioning
confidence: 91%